Dendritic cells in atherosclerotic inflammation: the complexity of functions and the peculiarities of pathophysiological effects - Chistiakov, Dimitry A.; Sobenin, Igor A.; Orekhov, Alexander N.; Bobryshev, Yuri V. (Frontiers in Physiology, 2014)
Atherosclerosis is considered as a chronic disease of arterial wall, with a strong contribution of inflammation. Dendritic cells (DCs) play a crucial role in the initiation of proatherogenic inflammatory response. Mature DCs present self-antigens thereby supporting differentiation of naïve T cells to effector cells that further propagate atherosclerotic inflammation. Regulatory T cells (Tregs) can suppress proinflammatory function of mature DCs. In contrast, immature DCs are able to induce Tregs and prevent differentiation of naïve T cells to proinflammatory effector T cells by initiating apoptosis and anergy in naïve T cells. Indeed, immature DCs showed tolerogenic and anti-inflammatory properties. Thus, DCs play a double role in atherosclerosis: mature DCs are proatherogenic while immature DCs appear to be anti-atherogenic. Tolerogenic and anti-inflammatory capacity of immature DCs can be therefore utilized for the development of new immunotherapeutic strategies against atherosclerosis.